FILM LEGENDA ROGOSELO (Penatas Angin dan Baron Skeber) SEBAGAI MEDIA PENGENALAN WISATA DAN SEJARAH DI KABUPATEN PEKALONGAN - Muhammad Haryanto; Ribut Achwandi; Inayatul Ulya; Amalia Fitri (LPPM Universitas Pekalongan, 2013)
This research is aimed to give one of the alternates to promote and develop the tourism, folklore, history and culture in Pekalongan sub-district through a promotion media, film. Besides, it’s hoped that the study of this research will give benefits and can be used as a consideration for the policy makers and the artists of Pekalongan sub-district to find out the solution for the development of tourism, folklore, history and culture in Pekalongan sub-district. Keywords: folklore, film, tourism